Agonist-stimulated phosphatidylinositol-3,4,5-trisphosphate generation by scaffolded phosphoinositide kinases - Choi, Suyong (Nat Cell Biol, 2016)
Generation of the lipid messenger phosphatidylinositol-3,4,5-trisphosphate (PtdIns(3,4,5)P(3)) is crucial for development, cell growth and survival, and motility, and it becomes dysfunctional in many diseases including cancers. Here we reveal a mechanism for PtdIns(3,4,5)P(3) generation by scaffolded phosphoinositide kinases. In this pathway, class I phosphatidylinositol-3-OH kinase (PI(3)K) is assembled by IQGAP1 with PI(4)KIIIα and PIPKIα, which sequentially generate PtdIns(3,4,5)P(3) from phosphatidylinositol. By scaffolding these kinases into functional proximity, the PtdIns(4,5)P(2) generated is selectively used by PI(3)K for PtdIns(3,4,5)P(3) generation, which then signals to PDK1 and Akt that are also in the complex. Moreover, multiple receptor types stimulate the assembly of this IQGAP1–PI(3)K signalling complex. Blockade of IQGAP1 interaction with PIPKIα or PI(3)K inhibited PtdIns(3,4,5)P(3) generation and signalling, and selectively diminished cancer cell survival, revealing a target for cancer chemotherapy.